1987
DOI: 10.1002/1097-0142(19870501)59:9<1677::aid-cncr2820590926>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Time trends and occupational differences in cancer of the testis in New Zealand

Abstract: The findings are reported from a New Zealand Cancer Registry-based case-control study involving 427 male patients with testicular cancer registered during the period 1979-1983 and aged 20 years or more at time of registration. Controls were also males chosen from the Cancer Registry with two controls per case, matched on age and year of registration. It was found that, as in other countries, persons in the upper social class groupings were at increased risk of testicular cancer. Persons in professional occupat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
28
2

Year Published

1990
1990
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 22 publications
3
28
2
Order By: Relevance
“…Other studies have suggested this difference may exist, but looked at shorter time periods and did not demonstrate statistical significance (Kolonel et al, 1982;McCredie et al, 1990 (Table II). Other studies (Davies, 1981) including a New Zealand study (Pearce et al, 1987) have shown a higher incidence of this malignancy in people of higher socio-economic status however this would not explain our findings as generally Maoris have lower socio-economic status than their White counterparts (Pomare et al, 1988).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Other studies have suggested this difference may exist, but looked at shorter time periods and did not demonstrate statistical significance (Kolonel et al, 1982;McCredie et al, 1990 (Table II). Other studies (Davies, 1981) including a New Zealand study (Pearce et al, 1987) have shown a higher incidence of this malignancy in people of higher socio-economic status however this would not explain our findings as generally Maoris have lower socio-economic status than their White counterparts (Pomare et al, 1988).…”
Section: Discussioncontrasting
confidence: 52%
“…The worldwide incidence has steadily increased since the beginning of this century (Senturia, 1987) and in New Zealand this trend is continuing (Pearce et al, 1987).…”
mentioning
confidence: 99%
“…In a U.K. report, a history of sexually transmitted disease and participation in certain sports was linked to a higher risk of nonseminoma cancers (21). The effect of socioeconomic status on testicular cancer is not conclusive, although men belonging to higher socioeconomic groups are often reported to be higher risk of testicular cancer relative to less-privileged groups (49,50). As with other variables, the risk estimates tend not, however, to be consistent by subtype (50).…”
Section: Discussionmentioning
confidence: 95%
“…High socioeconomic status has been reported to be associated with an increased risk of testis cancer. 26,27 Given the improvements in the standard of living for many populations over the past century, it is possible that some factors accompanying these changes in lifestyle is responsible for the increase in incidence. Increased maternal age and low parity have been suggested to be risk factors for testis cancer in some studies [28][29][30] and have also increased in prevalence in many populations over the past half-century.…”
Section: Discussionmentioning
confidence: 99%